2019
DOI: 10.1007/s10123-019-00112-1
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress on elucidating the molecular mechanism of plasmid-mediated colistin resistance and drug design

Abstract: Antibiotic resistance is a growing global challenge to public health. Polymyxin is considered to be the last-resort antibiotic against most gram-negative bacteria. Recently, discoveries of a plasmid-mediated, transferable mobilized polymyxin resistance gene ( mcr-1 ) in many countries have heralded the increased threat of the imminent emergence of pan-drug-resistant super bacteria. MCR-1 is an inner membrane protein that enables bacteria to develop resistance to polymyxin by transferring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 78 publications
0
20
0
Order By: Relevance
“…Previous studies have shown that all the members of the MCR family proteins possess an identical secondary structure, with a high degree of conservation for the amino acid residues in the active site and PEA-interacting cavities. In particular, residues Glu246, Thr285, His390, Asp465, and His466 in the zinc-binding core and residues Asn108, Thr112, Glu116, Ser330, Lys333, His395, and His478 in the PEA binding cavity in MCR-1 are also located in similar positions in other MCR members 47 . Although there is no cysteine residues in the active site of MCR enzyme, to our surprise, unlike Bi(III) drugs, AUR also targets MCR-1 protein at its zinc-catalytic core through the side-chains (εN) of histidine residues, suggesting that the "softness" of histidine (e.g., εN) is tunable by a protein.…”
Section: Col + Aur Colmentioning
confidence: 90%
“…Previous studies have shown that all the members of the MCR family proteins possess an identical secondary structure, with a high degree of conservation for the amino acid residues in the active site and PEA-interacting cavities. In particular, residues Glu246, Thr285, His390, Asp465, and His466 in the zinc-binding core and residues Asn108, Thr112, Glu116, Ser330, Lys333, His395, and His478 in the PEA binding cavity in MCR-1 are also located in similar positions in other MCR members 47 . Although there is no cysteine residues in the active site of MCR enzyme, to our surprise, unlike Bi(III) drugs, AUR also targets MCR-1 protein at its zinc-catalytic core through the side-chains (εN) of histidine residues, suggesting that the "softness" of histidine (e.g., εN) is tunable by a protein.…”
Section: Col + Aur Colmentioning
confidence: 90%
“…The electrostatic interaction between the cationic region of colistin, which is from the diamino-butyric acid (Dab) residues, and the negatively charged phosphate groups of lipid A, replace the magnesium and calcium ions previously united with the phosphate group. This destabilizes the lipid A and increases the permeability of the outer membrane, leading to the entry of colistin by a self-promoted uptake mechanism and eventual bacterial death [26,29]. Another antibacterial mechanism is the inhibition of a crucial respiratory enzyme, the type II NADH-quinone oxidoreductase (NDH-2) in the bacterial cell membrane [29].…”
Section: Colistin Resistance In Gram-negative Bacteriamentioning
confidence: 99%
“…To date, a small number of AMPs have been successfully employed clinically (e.g. polymyxin B, colistin and daptomycin) to treat drug-resistant infections, although in many cases their application is limited by the toxicity of the native compounds (Barros et al 2019;Kai and Wang 2020;Poirel et al 2017;Yu et al 2015).…”
Section: Introductionmentioning
confidence: 99%